Molecular Assessment of Microcirculation Injury in Formalin‐Fixed Human Cardiac Allograft Biopsies With Antibody‐Mediated Rejection. Issue 2 (2nd August 2016) - Afzali, B.; Chapman, E.; Racapé, M.; Adam, B.; Bruneval, P.; Gil, F.; Kim, D.; Hidalgo, L.; Campbell, P.; Sis, B.; Duong Van Huyen, J. P.; Mengel, M.
Abstract : Precise diagnosis of antibody‐mediated rejection (AMR) in cardiac allograft endomyocardial biopsies (EMBs) remains challenging. This study assessed molecular diagnostics in human EMBs with AMR. A set of 34 endothelial, natural killer cell and inflammatory genes was quantified in 106 formalin‐fixed, paraffin‐embedded EMBs classified according to 2013 International Society for Heart and Lung Transplantation (ISHLT) criteria. The gene set expression was compared between ISHLT diagnoses and correlated with donor‐specific antibody (DSA), endothelial injury by electron microscopy (EM) and prognosis. Findings were validated in an independent set of 57 EMBs. In the training set (n = 106), AMR cases (n = 70) showed higher gene set expression than acute cellular rejection (ACR; n = 21, p < 0.001) and controls (n = 15, p < 0.0001). Anti‐HLA DSA positivity was associated with higher gene set expression (p = 0.01). Endothelial injury by electron microscopy strongly correlated with gene set expression, specifically in AMR cases (r = 0.62, p = 0.002). Receiver operating characteristic curve analysis for diagnosing AMR showed greater accuracy with gene set expression (area under the curve [AUC] = 79.88) than with DSA (AUC = 70.47) and C4d (AUC = 70.71). In AMR patients (n = 17) with sequential biopsies, increasing gene set expression was associated with inferior prognosis (p = 0.034). These findings were confirmed in the validation set. In conclusion, biopsy‐based molecular assessment of antibody‐mediated microcirculation injury has the potential to improve diagnosis of AMR in human cardiac transplants. Abstract : This study assesses a set of 34 endothelial, natural killer cell and inflammatory genes for molecular diagnostics in human formalin‐fixed, paraffin‐embedded heart allograft biopsies, and suggests that biopsy‐based molecular assessment of antibody‐mediated microcirculation injury has the potential to improve diagnostics from cardiac transplants.